PENINGKATAN AKTIVITAS PEMBELAJARAN HIDROSFER DAN DAMPAKNYA TERHADAP KEHIDUPAN MELALUI TINDAKAN GURU INOVATIF PADA KELAS X DI SMA NEGERI 1 SEMARANG - Kun Marlina Lubis (Universitas Negeri Semarang, 2013)
Study process could be say success if could improve student result from cognitive,psicomotoric and affective aspect. The aims of this study were: 1) Improvingactivity in Action Class; 2) Creating study process based on active student. Thisresearch consist of three cycles, and each cycle consists of planning, action,observation and reflection. Result showed that in cycle I, innovative action fromthe teacher in Action Class could improve until more than 22%, which showed byresponse from 2 out of 9 exist activity indicators. In cycle II, student’s activityincrease 16,7% from cycle I or with other word, cycle II activity was more than86%. The significant improvement (more than 97%) or increase more than 27,8%got from cycle III. Based on research’s result, it could be confirmed that byinnovative action from the teacher between Action Class and Parallel Class, therewere no different in study activity of hydrosfer and its impact to daily life. Theconclusion said that each cycle improvement more than 33% got from innovativeaction of the teacher.